2016
DOI: 10.1111/ctr.12727
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of live donor pre‐transplant and recipient post‐transplant renal volumes

Abstract: Pre-transplant and post-transplant kidney volumes are correlated with post-transplant graft function, and graft growth is affected by the relative sexes of the recipient and donor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Hypertrophy of donated renal allografts after transplantation has been evaluated by several volumetric methods, including radioisotopes, Doppler ultrasonography, and 3D‐CT . Our previous study, together with others, demonstrated that the increase in allograft volume during the first year after transplantation correlated significantly with residual renal function in recipients . These findings indicate that 3D‐CT may be useful in screening for graft filtration overload, which is critical in determining allograft survival.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Hypertrophy of donated renal allografts after transplantation has been evaluated by several volumetric methods, including radioisotopes, Doppler ultrasonography, and 3D‐CT . Our previous study, together with others, demonstrated that the increase in allograft volume during the first year after transplantation correlated significantly with residual renal function in recipients . These findings indicate that 3D‐CT may be useful in screening for graft filtration overload, which is critical in determining allograft survival.…”
Section: Discussionmentioning
confidence: 76%
“…Earlier studies have used donor body surface area, donor body weight, renal graft weight and cross‐sectional renal area on ultrasound as surrogate markers of nephron mass . We previously reported that the mean volume of the pretransplant grafted kidney increased approximately 27% after transplantation, with graft growth being most prominent in grafts from female donors to male recipients . The increase in kidney volume likely reflects excess filtration, resulting from the concomitant enlargement of glomerular volume.…”
mentioning
confidence: 99%
“…27 Similar conflicting findings have been reported in studies using overall kidney volume as a surrogate for glomerular volume, based on imaging and histologic studies that show a significant correlation between overall kidney volume and glomerular volume. 25 Kidney size may increase in the first year after transplantation, particularly in female donor to male recipient transplants and child to adult transplants, 28 providing evidence that transplanted kidneys can adapt to increases in functional demand. El-Agroudy et al 23 reported that 5-y graft survival rates were lower in transplants from small body weight donors into large body weight recipients, suggesting that, clinically, glomerular hypertrophy resulting from increased functional demand may be maladaptive.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney volume as a surrogate marker of nephron mass and renal function has been presented by many authors as a good predictor of recipient renal function. Many studies to date have investigated donor factors associated with recipient renal function and outcomes, though scarce data are available about factors associated with donor's renal function after nephrectomy [9‐16].…”
Section: Introductionmentioning
confidence: 99%